Metabolit- och hormonnivåer som tidiga markörer för fruktsamhet och produktionsstörningar hos mjölkkor - Johansson, Karin (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2012)
During the last decades the fertility of dairy cows has declined in the same rate as the milk yield has increased. This is a result of the negative genetic correlation between milk yield and fertility, failure to show estrous signs and metabolic problems in the cow. The purpose of this review was to investigate the function of metabolites and hormones as markers for disturbances in fertility, health and production in the dairy cow. There are several metabolites that are suggested to indicate the cow’s energy balance. β-hydroxybutyrate (BHB), acetone, nonesterified fatty acids (NEFA), urea and glucose are metabolites that have been found to have connections to the energy status of the cow. BHB, NEFA and urea also is related to fertility. There are also some hormones that have been suggested to indicate energy status. Insulin and insulin-like growth factor-1 is mentioned in this study but have been found to have only weak connections to energy balance. By using endocrine parameters for fertility measures and estrous control the cow fertility may improve. Progesterone can be used for measurements of endocrine parameters such as interval from calving to commencement of luteal activity and also for detection of estrous. Estradiol can be used for estrous detection and anti-Müllerian hormone has been proposed for determining the young animal’s reproductive longevity. Progesterone, BHB and urea are used as indicators already today. According to this study some metabolites and hormones are more useful as indicators than others. BHB can be used as an indicator for both energy balance and fertility. Urea has more than one area of use as well, e.g. control of the protein/energy balance in the feed and indicator of fertility status. The hormone best suited for measures of fertility parameters is progesterone which can be used both for estrous control and detection of fertility disturbances. All these substances can be measured in the milk which is a requisite for using them on the farm.